Biofilm formation, pigment production and motility in Pseudomonas spp. isolated from the dairy industry. (April 2018) - Rossi, Chiara; Serio, Annalisa; Chaves-López, Clemencia; Anniballi, Fabrizio; Auricchio, Bruna; Goffredo, Elisa; Cenci-Goga, Beniamino Terzo; Lista, Florigio; Fillo, Silvia; Paparella, Antonello
Abstract: The aim of this study was to investigate the ability of Pseudomonas spp. strains isolated from milk, dairy products and dairy plants, to produce blue pigment in situ, to form biofilm onto polystyrene surfaces and to perform different types of motility. Molecular identification revealed that, out of 72 Pseudomonas spp. isolates, P . fluorescens was the most common species (50 isolates) followed by P . putida (9), P . koreensis (4), P . brenneri (4), P . aeruginosa (2), P . granadensis (2) and P . veronii (1). The evaluation of blue colour production showed that the pigment was produced at 10 °C but not at 30 °C; in addition this character was strain- and species-dependent, with only 16 P. fluorescens strains showing blue pigment production. Most of the studied strains produced biofilm although with some differences related to the strains and the incubation temperatures. Within the most abundant isolated species ( P . fluorescens ), about 46%, 34% and 26% of the strains were able to swim, swarm and twitch, respectively. The observed relationship between biofilm formation and blue pigment production in P . fluorescens strains was statistically significant. Since these characteristics may contribute to the persistence of microorganisms in food processing environments and therefore to the contamination of food products, our results may help to focus on the control of the strains involved in the blue discolouration of dairy products. Highlights: Pseudomonas fluorescens was the most common species among 72 isolates from dairy products and plants. Only 16 P. fluorescens strains produced blue pigment at 10 °C. Biofilm production was strain-dependent, with differences related also to incubation conditions. Great part of the strong biofilm producers were also blue pigment producers.